Mineral Contents of Some Wild Ascomycetous Mushrooms - Kaya, A.; Bag, H. (Asian Journal of Chemistry, 2012)
Minerals (Al, B, Cd, Co, Cr, Cu, Fe, Mn, Ni, Pb, Sn and Zn) contents of eight naturally growing ascomycetous mushrooms (Geopora arenicola, Geopora sumneriana, Helvella acetabulum, Helvella leucomelaena, Helvella leucopus, Mitrophora semilibera, Morchella elata and Morchella rigida) and the underlying soil samples, were determined by inductively coupled plasma optical emission spectroscopy (ICP-OES). In general, mineral contents of the fruit bodies are lower than the substrate soil, but Cd, Cu and Zn accumulation were found to be higher than the underlying soil in some mushrooms.